Odpowiedzialność jako kategoria podstawowa w prawie - Bechcicki, Sebastian (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
This article features responsibility in different perspectives, so it provides moderately complex explanation of the term. The definition offered within the text ranges from strict sense to the highest level of abstraction. It is a probe of the field of responsibility in a greater depth than usual, allowing to understand the meaning of responsibility as a basic category of law. Thesis laid open in the article goes beyond contemporary understanding of the term „responsibility”.
Keywords: responsibility; category; law; sociology